Morin ameliorates myocardial injury in diabetic rats via modulation of inflammatory pathways - Vipin Kumar Verma; Salma Malik; Ekta Mutneja; Anil Kumar Sahu; Vaishali Prajapati; Prashant Mishra; Jagriti Bhatia; Dharamveer Singh Arya (Laboratory Animal Research, 2024)
Abstract Background High blood glucose levels in diabetes lead to vascular inflammation which accelerates atherosclerosis. Herein, Morin was orally administered in male Wistar rats, at the dose of 40 mg/kg for 28 days, and on the 27th and 28th day, ISO was administered to designate groups at the dose of 85 mg/kg s.c., to induce myocardial infarction. Results Free radical generation, including ROS, in diabetes following ISO administration, leads to the activation of both intrinsic and extrinsic pathways of apoptosis. Morin significantly (p ≤ 0.05) reduced oxidative stress (GSH, MDA, SOD), cardiac injury markers (CK-MB, LDH), inflammation (TNF, IL-6), and apoptosis (Bax, BCl2, Caspase-3). In addition, it also reduced insulin and blood glucose levels. Akt/eNOS, Nrf2/HO-1, MAPK signaling pathways, and Insulin signal transduction pathways were positively modulated by morin pre-treatment. Conclusions Morin attenuated oxidative stress and inflammation and also modified the activity of various molecular pathways to mitigate cardiomyocyte damage during ISO-induced MI in diabetic rats.